Possible Motivations for Christians to Preserve Creation - May, Andreas (Studia Ecologiae et Bioethicae, 2024)
Three different aspects are presented that can motivate people to work for the preservation of creation. All three motivations are closely linked to Christianity, so that Christianity could become the key to solve the global problems. The three motivations are 1) the admiration and the praise of creation, 2) the personal relationship with the God of Christianity and 3) the planet Earth is precious because of Jesus Christ. The third motivation results from the incarnation, death and resurrection of Jesus Christ. Every suffering and death of every human being and every other living being gets its meaning, value and redemption through the suffering, death and resurrection of Jesus Christ. This is explained using the keywords enabling, participation, solidarity and resurrection. This salvation event took place on this planet and the Creator of the universe became a human being, a creature of this planet. Through this, all human beings, but also all the other living beings on Earth and even the entire planet Earth are sanctified in an extraordinary way. In this way, all living beings on Earth and the entire planet have an inalienable dignity and a supreme value that is established, defended and restored by the Creator of the universe.